Analisis Gaya Belajar Visual dan Auditori terhadap Motivasi Belajar di SMP Negeri 1 Greged - Octora, Kyana Listia; Rahmawati, Elin Maulida; Nurasih, Ai; Sangdiyah, Khalimatus (COUNSELIVE: Jurnal Konseling Kehidupan, 2025)
This research is motivated by the phenomenon of low student learning motivation in rural areas, particularly at SMP Negeri 1 Greged, which is still dominated by the implementation of conventional lecture-based learning methods. Based on initial observations, it was identified that the monotonous teacher-centered approach does not consider the diversity of student learning styles, thus potentially hindering the development of learning motivation, especially for students with a tendency towards visual and auditory learning styles. This study aims to analyze the effect of the application of visual and auditory learning styles on improving student learning motivation. The method used was descriptive qualitative with a case study design, implemented through participatory observation techniques, in-depth interviews, and documentation studies. The results of the study indicate that the multimodal learning intervention successfully transformed the learning environment to be more participatory and dynamic. The findings revealed significant improvements in four main aspects, namely: student activeness in group discussions, increased information retention through dual coding mechanisms, the development of courage to express oneself, and the creation of psychological safety in the learning process. Based on these findings, it can be concluded that understanding the diversity of learning styles and implementing a multimodal approach are key components in creating effective and inclusive learning, especially in rural areas. This study recommends the importance of integrating a learning style-based approach into pedagogical practices to improve student motivation and learning achievement.